A survey of tobacco dependence treatment guidelines in 121 countries - Piné-Abata, Hembadoon; McNeill, Ann; Raw, Martin; Bitton, Asaf; Rigotti, Nancy; Murray, Rachael (Wiley, 2013)
Aims To report progress among Parties to the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC) in developing national tobacco treatment guidelines in accordance with FCTC Article 14 guideline recommendations.